2021
DOI: 10.1172/jci142421
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-mediated depletion of viral reservoirs is limited in SIV-infected macaques treated early with antiretroviral therapy

Abstract: The effectiveness of virus-specific strategies, including administered HIV-specific mAbs, to target cells that persistently harbor latent, rebound competent HIV genomes during combination antiretroviral therapy (cART) has been limited by inefficient induction of viral protein expression.To examine antibody-mediated viral reservoir targeting without a need for viral induction, we used an anti-CD4 mAb to deplete both infected and uninfected CD4 + T cells. Ten rhesus macaques infected with barcoded SIVmac239M rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 64 publications
5
30
0
Order By: Relevance
“…Blood was collected in EDTA tubes and plasma was separated by density gradient centrifugation and used for the determination of plasma VLs by SIVgag RT-qPCR at NIRC or at Leidos (Quantitative Molecular Diagnostics Core, AIDS and Cancer Virus Program, Frederick National Laboratory). Tissue VLs from snap-frozen colorectal bx and LN FNAs were performed at Leidos (A14X004, A14X005, and A14X013) as described ( 78 ) or, for the remaining macaques and from PBMCs of all macaques, they were performed as described ( 77 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected in EDTA tubes and plasma was separated by density gradient centrifugation and used for the determination of plasma VLs by SIVgag RT-qPCR at NIRC or at Leidos (Quantitative Molecular Diagnostics Core, AIDS and Cancer Virus Program, Frederick National Laboratory). Tissue VLs from snap-frozen colorectal bx and LN FNAs were performed at Leidos (A14X004, A14X005, and A14X013) as described ( 78 ) or, for the remaining macaques and from PBMCs of all macaques, they were performed as described ( 77 ).…”
Section: Methodsmentioning
confidence: 99%
“…Blood was collected in EDTA tubes and plasma was separated by density gradient centrifugation and used for the determination of plasma VL by SIVgag qRT-PCR at NIRC or at Leidos (Quantitative Molecular Diagnostics Core, AIDS and Cancer Virus Program Frederick National Laboratory). Tissue VL from snap frozen colorectal biopsies and LN FNA were performed at Leidos (A14X004, A14X005 and A14X013) as described in( 100 ) or, for the remaining macaques and from PBMC of all macaques they were performed as described in ( 99 ).…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, we have previously shown that the barcode remains intact during several months of replication and have not found any indication that different variants, which are isogenic except for the barcode sequences, differ in their replicative capacity [ 26 ]. The ability to quantify the replication of thousands of individual clonal variants greatly increases analytic resolution into the structure of the virus population, allowing detection of nuanced changes to its composition [ 34 ], and provides a way to directly estimate the rate of reactivation from latency for individual animals [ 26 , 38 ].…”
Section: Introductionmentioning
confidence: 99%